2019
DOI: 10.1021/acs.jpca.9b02580
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Spin Symmetry Conservation Studied for Symmetric Top Molecules (CH3D, CHD3, CH3F, and CH3Cl) in Supersonic Jet Expansions

Abstract: We report results on nuclear spin symmetry conservation studied by high resolution spectroscopy of relative line intensities for the A and E nuclear spin isomers of symmetric top molecules CHD 3 , CH 3 D, CH 3 F, and CH 3 35 Cl in supersonic jet expansions with He and Ar as carrier gases. Infrared absorption spectra were measured around 3000 cm −1 by an infrared (lead salt) diode laser and a continuous wave IR-OPO (infrared optical parametric oscillator) locked to a frequency comb. A detailed analysis of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The meta (A) isomer relaxes towards J = 0, the ortho (F) isomer to J = 1, and the para (E) isomer to J = 2 without interconversion [24,27,[75][76][77]. Similar results are obtained for the methane isotopomers CH 3 D and CHD 3 , and for CH 3 F, CH 3 Cl [20], and NH 3 [45]. For H 2 O it is found that at high dilution in the expansion (with Argon and with paramagnetic Oxygen) nuclear spin symmetry is conserved, whereas at high concentrations with possibly substantial cluster formation in the jet some interconversion between nuclear spin isomers occurs [139,140] (see also the recent review [141]).…”
Section: Const Fit I Fit Ii Fit Iii [54]supporting
confidence: 73%
See 4 more Smart Citations
“…The meta (A) isomer relaxes towards J = 0, the ortho (F) isomer to J = 1, and the para (E) isomer to J = 2 without interconversion [24,27,[75][76][77]. Similar results are obtained for the methane isotopomers CH 3 D and CHD 3 , and for CH 3 F, CH 3 Cl [20], and NH 3 [45]. For H 2 O it is found that at high dilution in the expansion (with Argon and with paramagnetic Oxygen) nuclear spin symmetry is conserved, whereas at high concentrations with possibly substantial cluster formation in the jet some interconversion between nuclear spin isomers occurs [139,140] (see also the recent review [141]).…”
Section: Const Fit I Fit Ii Fit Iii [54]supporting
confidence: 73%
“…The resolution of the monochromator around 1000 cm −1 is 1.5 cm −1 , when the widths of the entrance and exit slits are both 1 mm and at least one half of the grating is illuminated by the laser beam. This resolution is good enough to separate [20,21,82]).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations